Evaluation and obstacle factors of marine resources and environment carrying capacity in Beibu Gulf Urban Agglomeration - Li, Yan; Sun, Liang; Wu, Zongnan; Liu, Hong (Frontiers in Marine Science, 2023)
With the strong support of the Chinese government, the Beibu Gulf Urban Agglomeration has responded positively to the national call to vigorously develop the marine economy. However, a series of marine resource and environmental problems such as over-exploitation of marine resources and excessive discharge of marine pollutants in the Beibu Gulf Urban Agglomeration has also arisen along with the rapid development of the marine economy, limiting the space for the development of the marine economy in the Beibu Gulf Urban Agglomeration. Based on the panel data of seven coastal cities in the Beibu Gulf urban agglomeration from 2011-2021, the DPSIR model was used to construct a marine resources environmental carrying capacity evaluation index system including five dimensions of driving force, pressure, state, impact and response, and the TOPSIS model with combined weighting was used to make a comprehensive evaluation of the marine resources carrying capacity of the Beibu Gulf urban agglomeration, and then the barrier degree model was used to explore the barriers to the carrying capacity of marine resources and environment in the Beibu Gulf Urban Agglomeration. The empirical results show that, on the whole, the marine resources and environment carrying capacity of the seven coastal cities in the Beibu Gulf Urban Agglomeration show an upward trend. From the situation of each subsystem, the pressure subsystem and response subsystem have greater evaluation values, while the evaluation of the driving force, state, and influence subsystem needs to be improved; from the analysis of obstacle factors, the main single indicator obstacle factors include per capita coastline length, total import and export volume, and port cargo throughput, etc. The status subsystem is the main classification indicator barrier factor affecting the improvement of the marine resource and environmental carrying capacity of the Beibu Gulf Urban Agglomeration. Based on the results of the empirical analysis, corresponding suggestions are put forward.